Behavioral Change in First Time Expectant Fathers' Aggression - Davis, Helen V. (2002)
Thirty-two first time expectant fathers, 23-38 years of age, were recruited on a voluntary basis. They were tested on several behavioral measures throughout the course of their wives’ pregnancy. The Aggression Inventory (AI) was utilized during the first and third trimesters of the pregnancy in order to determine whether or not men become more aggressive over the course of a woman’s pregnancy. A two-way repeated measure Analysis of Variance (ANOVA) was utilized. The Wilks’ Lambda Multivariate test of effect for time yielded an F of .186. At an alpha level of .05, it was not significant. The Wilks’ Lambda multivariate test of effect for the subscales yielded an F of 10.951, which was a significant main effect at an alpha level of .05. Finally, when testing for an interaction between time and subscales the Wilks’ Lambda multivariate tests yielded an F of 1.024. It was not significant. Therefore, it appears that there is not a significant increase in aggression in males over the course of a pregnancy. However, there were significant limitations to this study